دور الأحداث الصّادمة في ظهور الاضطرابات النّفسية والصّلابة النّفسية لدى المرأة الجزائرية المهاجرة - بوقاسي وردة (Universty Of El-oued جامعة الوادي, 2024)
الملخص: ملخّص الدّراسة يتناول البحث التّالي إشكالية اختلاف استجابات المرأة الجزائريّة في الهجرة بعد التّعرّض لأحداث مولّدة للصّدمة النّفسية، البعض منهنّ يصبن باضطرابات نفسية مختلفة، والبعض الآخر منهن يقاومن ويتجاوزن دون مخلّفات مَرَضية قد تصل لتطوير صلابة نفسية، لذلك سنحاول من خلال البحث الحالي معرفة مختلف الاستجابات النّاتجة عن مجموعة من المحتويات والعناصر المتشابكة. ومن أجل تحقيق أهداف البحث، تمّ التّصميم والاعتماد على إجراءات منهجيّة تمثّلت في منهج دراسة الحالة لقدرته على التعبير عن المشاعر الإنسانية، ومن خلاله تمّ الاعتماد على مجموعة من الأدوات، كالمقابلة العيادية النصف موجهة، فقد تمّ تصميم كلّ مقابلة عياديه بمجموعة من المحاور، ويحتوي كل محور بدوره على مجموعة من الأسئلة بهدف جمع البيانات الضّرورية وذلك للإجابة على أهداف البحث. كما تمّ الاعتماد على الملاحظة العيادية ومجموعة من المقاييس النّفسية المتمثلة في مقياس الصّحة النّفسية ومقياس الصّلابة النّفسية، كمؤشّرات من أجل التّحقّق ممّا تمّ توصل إليه من نتائج دراسة الحالات، وتوصلت الدّراسة إلى النتائج التالية: تؤدي الأسباب النّفسية للمرأة الجزائرية إلى الهجرة، كما تساهم العوامل الاقتصادية دورها مهما في ذلك. لا تؤدّي الخبرات الصّادمة في ظهور الاضطرابات النّفسية حاليا، لدى المهاجرة الجزائرية. تساهم الخبرات الصادمة في تطوير الصّلابة النّفسية حاليا، لدى المهاجرة الجزائرية. تساهم الصّلابة النّفسية في تجاوز الضغوط النّفسية لدى المهاجرة الجزائرية. Abstract The following research addresses the problem of the different responses of Algerian women to immigration after exposure to an event that generates psychological trauma. Some of them develop various psychological disorders, while others resist and overcome without any pathological remnants that may lead to the development of psychological toughness. Therefore, through the current research, we will try to find out the various responses resulting from a group of intertwined contents and elements. In order to achieve the research objectives, methodological procedures were designed and relied upon, represented by the case study approach due to its ability to express human feelings, and through it a set of tools were relied upon, such as the semi-directed clinical interview. Each clinical interview was designed with a set of axes, and each axis in turn contains A set of questions with the aim of collecting the necessary data to answer the research. Objectives Clinical observation and a set of psychological measures, represented by the Mental Health Scale and the Psychological Hardiness Scale, were also relied upon as indicators in order to verify the results of the case studies. The study reached the following results: Psychological reasons lead Algerian women to migrate, and economic factors also play an important role in this. Traumatic experiences do not lead to the emergence of psychological disorders currently in the Algerian immigrant. Traumatic experiences currently contribute to the development of sychological toughness among Algerian immigrants. Psychological toughness contributes to overcoming psychological pressures among Algerian immigrants.
أطروحة دكتوراه تخصص علم النفس العيادي في العلوم الاجتماعية والإنسانية
Keywords: المرأة الجزائريّة في الهجرة، الصلابة النفسية، الصدمة النفسية.; Psychological trauma psychological toughness-Immigration Algerian women -